Pemanfaatan smartphone sebagai media pembelajaran ramah anak di Kabupaten Halmahera Selatan - Hi Karim, Kodrat; Purnomo, Eko; Kasim, Suhardi; Hi Panu, Rasmi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Child-friendly learning is designed to create a conducive learning environment, enabling children to learn effectively in a safe, non-threatening, and encouraging atmosphere. This project aims to optimize smartphone use among students at Public Elementary School 244 HALSEL, Gintang, utilizing concepts that are engaging and easy for students to grasp. This ensures more effective and impactful use of smartphones in achieving learning outcomes. The activities, conducted in September 2023, involved 30 students from grades 3 to 6. The methods employed were lectures and demonstrations to educate students on wise and child-friendly smartphone usage. The study reveals significant changes in smartphone usage post-socialization. The average daily use decreased from 4 hours to 3 hours, with the percentage for entertainment dropping from 75% to 50%, while usage for learning purposes increased from 25% to 50%. The average scores in English vocabulary tests rose from 60 to 75, indicating the positive effects of directed smartphone use. Students' awareness of responsible usage increased from 40% to 80%, and the average number of learning apps used per student rose from 1 to 3. Interactions between the team and students showed that most students owned social media accounts and used smartphones without parental supervision. These activities enhanced students' motivation and interest in learning, strengthened their understanding of smartphone usage in education, and cultivated awareness of the importance of wise usage. This project underscores the necessity of education and collaboration among schools, teachers, and parents in managing smartphone use by elementary school children, ensuring the maximum benefits of this technology in learning.